MODELING A VEHICLE’S SECURITY IN AN AUTONOMOUS VEHICLE SYSTEM - Manish Kumar (International Journal of Multidisciplinary Research and Studies, 2021)
It is very likely that the future of transportation will consist of automated vehicle systems. Many cars now have the capability to connect with one another through the use of a wireless channel thanks to the development of vehicle ad-hoc networks (VANETS). The real time application of a vehicle platoon, in which 8-25 cars follow one another and mimic the actions performed by the vehicle in front of it, is relatively new. However, the concept of a vehicle platoon was first introduced in 1986 as part of a project called PATH (Partners for Advanced Transit and Highways) that demonstrated the advantages of a vehicle platoon. Both a Cyber-Physical System (CPS) and an Internet of Things (IoT) system can be construed to refer to the same thing: an autonomous vehicle. [Cyber-Physical System] Cyber-Physical Systems (CPS) are sophisticated, heterogeneous, distributed systems that generally consist of a large number of sensors and actuators that are connected to a pool of processing nodes.